Self-Efficacy-Based Teacher Ability In Improving The Quality Of Akidah Akhlak Learning At Mts Darul Amin Palangka Raya - Nursetyowati, Rina; Hamdanah, Hamdanah; Mila, Mila (Institut Agama Islam An-Nawawi Purworejo, 2024)
This research was conducted at Madrasah Tsanawiyah Darul Amin Kota Palangka Raya with the aim of identifying the relationship between teacher self-efficacy and the quality of moral and ethics learning and time discipline. Teachers with high self-efficacy are able to create a positive and productive learning environment, increase learner activity, and apply more varied and effective learning methods. However, this study also found that teachers' tendency to follow students' preferences can hinder deep understanding of the material and reduce innovation in teaching. Reliance on student preferences risks creating stagnation in learning quality. Therefore, professional training for teachers is needed to increase their self-efficacy, so that they are able to balance students' needs with the application of deep learning principles. Thus, teachers can design learning that is not only fun but also educational, preparing students to face future challenges. The method used in this research is qualitative with a descriptive approach, where data is collected through observation, interview, and documentation techniques. Data analysis was conducted using triangulation techniques to ensure the validity of the information.